Norwich - British Archaeological Association.
1 online resource (392 pages).
Keywords: The importance of Norwich as the second city of England for 500 years is explored in this volume in nineteen essays and seven site reports. Current understanding of the city's origins and development is largely informed by the results of four decades of archaeological investigation. This work is reviewed and extended by the two introductory papers in this volume. A remarkable amount of the physical evidence of the city's prestigious status is extant, notably the cathedral and castle, two of the most ambitious Romanesque buildings in Europe. These are addressed in several papers, either by means of direct architectural study or in relation to issues such as patronage and influence. Norwich's outstanding parish churches and merchant houses, both barometers of continuity and change across the medieval and early modern periods, are the subject of five further papers. Norwich was a major centre of operations for masons, painters and artists of all kinds. This is explored not only within the city and cathedral precinct but through its impact in the county. Site reports, short essays on some of the buildings visited during the conference, further illuminate the role of Norwich-based designers and makers in the region.